Transition to fatherhood among first-time expectant fathers having couvade syndrome in northern Thailand: A grounded theory study - Sritawan, Piyawan; Sansiriphun, Nantaporn; Deeluea, Jirawan; Chaloumsuk, Nonglak; Krikitrat, Preeyakamon (Belitung Nursing Journal, 2026)
Background: Transitioning to fatherhood for the first time is a significant milestone in a man’s life, especially among first-time expectant fathers having couvade syndrome, which causes them to experience changes both physically and psychologically. However, there is a lack of existing research on the process of transition to fatherhood among first-time expectant fathers having couvade syndrome. Objective: This study aimed to explore the process of transition to fatherhood among first-time expectant fathers having couvade syndrome. Methods: This study adopted a constructivist grounded theory methodology. Participants included 20 first-time expectant fathers having couvade syndrome who were purposively selected from antenatal clinics of two hospitals in northern Thailand. Data were collected between March 2021 and October 2023 using in-depth interviews following Charmaz’s steps. Data were corrected and analyzed until theoretical saturation. Results: “Evolving new father’s role over couvade syndrome” emerged as the core category representing their transition into fatherhood. This process consisted of three phases. Phase I was experiencing couvade syndrome that involved confirming couvade syndrome and responding to couvade syndrome. Phase II focused on handling couvade syndrome by accepting it and adapting behaviors. Phase III was stepping into the father’s role as couvade syndrome symptoms resolved, encompassing freaking out about the new father’s role, dealing with it, and planning for raising the baby. Conclusion: This study generated new knowledge regarding the transition to fatherhood among first-time expectant fathers experiencing couvade syndrome that involves three phases: in early pregnancy, around the middle of pregnancy, and towards the end of pregnancy. The insights can be used to inform nursing interventions to provide comprehensive, phase-specific antenatal care for these fathers.